2019
DOI: 10.1101/636720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dose-dependent functions of SWI/SNF BAF in permitting and inhibiting cell proliferationin vivo

Abstract: 20SWI/SNF complexes regulate transcription through chromatin remodeling and opposing gene silencing by Polycomb-group (PcG) proteins. Genes that encode SWI/SNF subunits are 22 frequently mutated in human cancer. The selective advantage, subunit bias, and common heterozygosity of such mutations remains poorly understood. Here, we characterized how 24 functional loss of various SWI/SNF subunits and PcG EZH2 affect proliferation-differentiation decisions in vivo, making use of the reproducible development of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Consistent with this, the addition of PBRM-1 degradation in the mesoderm produced a phenotype that resembled maternal and zygotic loss of pbrm-1 function in the somatic gonad. Our observations are consistent with a previous study that showed dose-dependent functions of the SWI/SNF complex in the regulation of cell division in the M mesoblast: incomplete loss of swsn-1 via Cre/lox recombination or GFPnanobody-directed protein degradation produced an over-proliferation phenotype, while the combination of both produced an under-proliferation phenotype (van der Vaart et al 2020). Together, these two studies argue strongly for the use of both genetic deletion and protein degradation to produce a strong loss of gene function in specific tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this, the addition of PBRM-1 degradation in the mesoderm produced a phenotype that resembled maternal and zygotic loss of pbrm-1 function in the somatic gonad. Our observations are consistent with a previous study that showed dose-dependent functions of the SWI/SNF complex in the regulation of cell division in the M mesoblast: incomplete loss of swsn-1 via Cre/lox recombination or GFPnanobody-directed protein degradation produced an over-proliferation phenotype, while the combination of both produced an under-proliferation phenotype (van der Vaart et al 2020). Together, these two studies argue strongly for the use of both genetic deletion and protein degradation to produce a strong loss of gene function in specific tissues.…”
Section: Discussionsupporting
confidence: 93%
“…The CRY2 variant used, CRY2(olig), contains an E490G mutation to increase clustering ability (Taslimi et al, 2014). The GFP nanobody (VHH(GFP)) sequence was PCR amplified from plasmid pVP130 (Vaart et al, 2020), which was codon-optimized from the original sequence (Wang et al, 2017). The Pwrt-2 promotor was amplified from plasmid pRS177, the Pelt-2 promoter was amplified from plasmid pSMR12, the Phsp-16.48 promoter from plasmid pJRK83, and the par-6 coding sequence from pJRK11.…”
Section: Introductionmentioning
confidence: 99%